Intellectuals in the modern Islamic world transmission, transformation, communication - Dudoignon, Stephane A.; Komatsu, Hisao; Kosugi, Yasushi (New horizons in Islamic studies, 2006)
History of intellectuals in the Islamic world throughout the 20th century. This book provides diachronic analysis of different forms of communication, learning, and authority. It presents cases with historically and geographically different background, disclosing commonalities, similarities and intellectual echoes through its comparative approach.